Comparison Between the Runge Kutta Method and Euler Method for Solving Dengue Fever Disease Model - Mohamad Razapi , Muhammad Fikreey; Mohamad, Mahathir (Enhanced Knowledge in Sciences and Technology, 2025)
Dengue fever remains a global health challenge due to its rapid transmission and severe complications. This study evaluates two numerical methods, Euler and fourth-order Runge-Kutta (RK4), for solving a dengue fever disease model. Utilizing the SEIR framework, the research highlights the RK4 method’s superior accuracy and stability compared to Euler’s simplicity and computational efficiency. These findings underscore the importance of selecting appropriate numerical techniques for reliable epidemiological modeling, aiding in better-informed public health interventions.